Unsolved Questions Regarding EU Citizens Access to Public Healthcare Services in Spain - Alejandra Boto (Central European Public Administration Review)
Spain is nowadays living the echoes of economic crisis adopting measures to boost employment figures and to correct the excessive macroeconomic imbalances. This paper reviews previous research findings on how these policies affect European citizenship and the access to welfare systems, healthcare provision in particular.